Efficacy of endovascular circulating false lumen occlusion in chronic aneurysmal descending aortic dissections - Emeric Gremen; Mathieu Finas; Eliott Mathieu; Frédéric Thony; Mathieu Rodiere; Julien Ghelfi (Diagnostic and Interventional Radiology, 2025)
PURPOSE: To evaluate the efficacy of endovascular circulating false lumen occlusion (CFLO) in inducing positive aortic remodeling in chronic aneurysmal descending aortic dissection (AD). METHODS: This retrospective monocentric study included patients treated by CFLO between 2003 and 2022 in the context of chronic AD with progressive descending aneurysmal evolution and persistent circulating false lumen (FL). The procedure was achieved with coils, plugs, and/or glue at the entry tear or in the FL and/or with covered stenting in the supra-aortic trunk. The primary endpoint evaluated the positive aortic remodeling, defined as stabilization or a decrease in the aortic diameter on a computed tomography scan at the 1-year follow-up after the procedure. The FL circulating status, safety, and occurrence of aneurysm events during follow-up were also evaluated. RESULTS: Twenty patients [median age: 65.4 years, interquartile range (IQR): 58.4–69.9; 13 men] were included, with a median duration from an acute AD of 32.5 months (IQR: 8.8–76.5). Twelve patients (60%) achieved complete FL thrombosis after CFLO, whereas 8/20 patients (40.0%) experienced partial thrombosis. Additionally, positive aortic remodeling was observed in 13 patients (65%). Following the procedure, the aneurysmal aortic diameter decreased in 8/20 patients (40.0%) and remained stable in 5/20 patients (25.0%). Two patients (10%) had complications related to the procedure. Two patients (10%) had secondary aneurysm events during follow-up. CONCLUSION: CFLO is a feasible and efficient method to induce FL thrombosis and reduce aneurysmal progression in chronic AD. CLINICAL SIGNIFICANCE: The positive outcomes observed highlight the potential of this technique to improve patient management in complex aortic pathologies. This approach offers a valuable option in the management of chronic AD and emphasizes the importance of endovascular interventions in enhancing patient outcomes.